Takhraj Adth dalam Buku Pendidikan Agama Islam dan Budi Pekerti Kurikulum 2013 SMP Kelas VII - Fauziyah, Malihatul (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2014)
The paper describes the use of Hadith is a course book for junior high schools.As we know that Hadith is the second source of Islamic teachings after the Koran,therefore the study of Hadith especially Hadith Ahadis very important. ExaminingHadith is an effort to avoid the use of arguments that do not really come fromthe Prophet Muhammad. So it is necessary to know the technical analysis of thequality of Hadith, where the sadhuses the opinion of al-Shafiâ€™i and the al-jará¸¥wa al-taâ€˜dÄ«l uses the opinion of Ibn á¸¤ajar al-â€˜AshqalÄniy.The number of Hadithused the book Pendidikan Agama Islam dan Budi Pekerti 2013 Curriculum forjunior high schools Class VII written by Mustahdi and Sumiyati is 19 Hadith; andthere are 105 references. Of 19 Hadith, 8 hadith are á¹£aá¸¥Ä«á¸¥ li dhÄtihi, 6 Hadith areá¸¥asan li dhÄtihi, and 5 Hadith are á¸aâ€˜Ä«f. We can use á¹£aá¸¥Ä«á¸¥ li dhÄtihi dan á¸¥asan lidhÄtihias arguments, but not á¸aâ€˜Ä«f.